2020 42nd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2020
DOI: 10.1109/embc44109.2020.9175478
|View full text |Cite
|
Sign up to set email alerts
|

Lung Region Segmentation in Chest X-Ray Images using Deep Convolutional Neural Networks

Abstract: Lung cancer is, by far, the leading cause of cancer death in the world. Tools for automated medical imaging analysis development of a Computer-Aided Diagnosis method comprises several tasks. In general, the first one is the segmentation of region of interest, for example, lung region segmentation from Chest X-ray imaging in the task of detecting lung cancer. Deep Convolutional Neural Networks (DCNN) have shown promising results in the task of segmentation in medical images. In this paper, to implement the lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Lunit INSIGHT CXR (Lunit) is a commercially available deep-learning algorithm-based CDSS for the automatic detection of thoracic abnormalities on chest X-ray (CXR). Recent studies have reported that AI systems using deep learning techniques can detect various diseases on CXRs, showing performance comparable to that of expert radiologists [ 3 9 ]. In previous studies, Lunit showed excellent diagnostic performance, which was similar to that of expert radiologists, and improved the performance of physicians in diagnosing pneumonia, lung cancer, tuberculosis, and multiple abnormal findings [ 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lunit INSIGHT CXR (Lunit) is a commercially available deep-learning algorithm-based CDSS for the automatic detection of thoracic abnormalities on chest X-ray (CXR). Recent studies have reported that AI systems using deep learning techniques can detect various diseases on CXRs, showing performance comparable to that of expert radiologists [ 3 9 ]. In previous studies, Lunit showed excellent diagnostic performance, which was similar to that of expert radiologists, and improved the performance of physicians in diagnosing pneumonia, lung cancer, tuberculosis, and multiple abnormal findings [ 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning models learn feature representation independently and utilize the learned highdimensional abstraction to finalize segmentation tasks without manual intervention (20). Recently, several studies have proposed various deep learning based automatic segmentation techniques for lung cancer (34)(35)(36)(37)(38)(39)(40)(41)(42). There is not yet a review of deep learning based automatic segmentation techniques for lung cancer radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Convolutional neural networks (CNNs) have brought about a revolution in the feld of DL, with their incredible success in various domains such as image classifcation [20], object detection [21], and image segmentation [22]. As a result, there has been a signifcant increase in interest from both academia and industry in recent years.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%